2016
DOI: 10.1007/s10433-016-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

How aging affects self-reports

Abstract: A lot of information used in aging research relies on self-reports. Surveys or questionnaires are used to assess quality of life, attitudes toward aging, experiences of aging, subjective well-being, symptomatology, health behaviors, financial information, medication adherence, etc. Growing evidence suggests that older and younger respondents are differentially affected by questionnaire features and the cognitive tasks that question answering pose. This research has shown that age-related changes in cognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 42 publications
1
72
1
3
Order By: Relevance
“…Another consideration that might explain the weak results for explanatory factors is that well-being and perceived stress may be biased by age-related differences in self-reporting, a concept that has recently been discussed [24,25]. Older age may affect self-reports, because age is associated with decreased memory capacity, differences in how questions are interpreted, less responsiveness to context effects, more difficulty with open-ended questions, and difficulty interpreting numeric response options (32).…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration that might explain the weak results for explanatory factors is that well-being and perceived stress may be biased by age-related differences in self-reporting, a concept that has recently been discussed [24,25]. Older age may affect self-reports, because age is associated with decreased memory capacity, differences in how questions are interpreted, less responsiveness to context effects, more difficulty with open-ended questions, and difficulty interpreting numeric response options (32).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the questionnaires did not contain more details of the subjects' self-treatment behaviour, such as the specific form of self-treatment of each respondent, and the type of the medicine used in the self-treatment. Self-reported information may also lead to some reporting bias or recall bias because the majority of the respondents are elders [65]. In addition, the potential seasonal variation in healthy condition as well as in the health-seeking pattern is unavoidable, especially for the elders, which may limit the generalisability of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…It should be noted that we measured environmental factors by asking patients to subjectively evaluate their stair, floor, bathroom, and corridor conditions. In other studies, age significantly influences the way participants respond to self-reported questions due to the changes of cognitive and communicative functioning, as well as working memory capacity [36,37]. With cognitive decline, older people might face difficulties in recalling the conditions or behaviors mentioned in the questions [38,39], which leads to less accurate answers [40].…”
Section: Discussionmentioning
confidence: 99%